2015
DOI: 10.1007/s10551-015-2855-2
|View full text |Cite
|
Sign up to set email alerts
|

Does Ethical Image Build Equity in Corporate Services Brands? The Influence of Customer Perceived Ethicality on Affect, Perceived Quality, and Equity

Abstract: In the current socioeconomic environment, brands increasingly need to portray societal and ethical commitments at a corporate level, in order to remain competitive and improve their reputation. However, studies that relate business ethics to corporate brands are either purely conceptual or have been empirically conducted in relation to the field of products/goods. This is surprising because corporate brands are even more relevant in the services sector, due to the different nature of services, and the subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(114 citation statements)
references
References 151 publications
7
92
0
8
Order By: Relevance
“…For example, buying a hybrid car not only improves the environment, but also enables savings on fuel. Some works show that CSR is an attribute of brand personality associated with a perception of better quality (Liu, Wong, Shi, Chu, & Brock, 2014;Sierra, Iglesias, Markovic, & Singh, 2017). Some works show that CSR is an attribute of brand personality associated with a perception of better quality (Liu, Wong, Shi, Chu, & Brock, 2014;Sierra, Iglesias, Markovic, & Singh, 2017).…”
Section: Csr As a Generator Of Value For Consumersmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, buying a hybrid car not only improves the environment, but also enables savings on fuel. Some works show that CSR is an attribute of brand personality associated with a perception of better quality (Liu, Wong, Shi, Chu, & Brock, 2014;Sierra, Iglesias, Markovic, & Singh, 2017). Some works show that CSR is an attribute of brand personality associated with a perception of better quality (Liu, Wong, Shi, Chu, & Brock, 2014;Sierra, Iglesias, Markovic, & Singh, 2017).…”
Section: Csr As a Generator Of Value For Consumersmentioning
confidence: 99%
“…As defined, utilitarian value is analogous to the notion of the quality-price ratio (Sweeney & Soutar, 2001). Some works show that CSR is an attribute of brand personality associated with a perception of better quality (Liu, Wong, Shi, Chu, & Brock, 2014;Sierra, Iglesias, Markovic, & Singh, 2017). In other words, the holistic perception that the brand is socially responsible can transfer to the product-service level through an increase in perceived quality.…”
Section: Csr As a Generator Of Value For Consumersmentioning
confidence: 99%
“…Loyalty is behaviour that can be observed and is reflected in consumers' attitudes and the way in which they advertise a company or a product through word-of-mouth recommendation (Garcia de los Salmones et al, 2005). Individuals may prove their loyalty to a company by repurchasing one of its products or services, by remaining immune to the marketing efforts of the other competitors (Sierra et al, 2015), as well as by recommending the company and increasing the frequency of visits and/or the purchased quantity of goods (Dabija and Băbuþ, 2012;Swoboda et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Concerning the outcomes of brand emotions, some scholars have demonstrated that brand emotion could significantly influence a customer's behavior towards a product. For example, brand emotion influences purchase intention [20], brand equity [21], and brand loyalty [22,23]. Brand emotion also strongly influences brand extension [24].…”
Section: H2: Alternative Attractiveness Positively Influences Negativmentioning
confidence: 99%